Efficient synthesis of 2, 6-bis(hydroxymethyl)pyridine using whole-cell biocatalysis. Issue 9 (21st April 2022) - Kardashliev, Tsvetan; Panke, Sven; Held, Martin
Abstract : We demonstrate a novel one-pot biocatalytic process for the preparation of a versatile chemical intermediate, 2, 6-bis(hydroxymethyl)pyridine, from naturally-occurring 2, 6-lutidine using recombinant microbial whole cells as catalysts. Abstract : We demonstrate a novel one-pot biocatalytic process for the preparation of a versatile chemical intermediate, 2, 6-bis(hydroxymethyl)pyridine, from naturally-occurring 2, 6-lutidine using recombinant microbial whole cells as a catalysts. After scale up, the bioconversion enabled titers exceeding 12 g L −1 with a space–time yield of 0.8 g L −1 h −1 . This biocatalytic route offers a simpler and more sustainable alternative to multistep organic synthesis protocols.